Mid-century [videorecording (DVD)] - Stern, Mike (Producer); Stern, Mike (Producer); West, Shane; Hay, Sarah, 1987-; Gilligan, Chelsea; Sriram, Annapurna; Dumbfoundead, 1986-; Williams, Vanessa, 1963-; Perry, Emmy, 2004-; Dern, Bruce; Lang, Stephen, 1952- (Lionsgate, 2022)
A husband and wife's weekend in a mid-century modern vacation rental turns deadly when the husband discovers the owner is a psychopath with a backyard of buried secrets and designs on his wife.